Edukasi Pentingnya Peran Perekam Medis Di Fasilitas Pelayanan Kesehatan Pada Siswa SMKS Real Informatika - Desfa Anisa; Fani Farhansyah; Delia Altesa Putri (CV. Multi Kreasi Media, 2024)
One of the human resources in hospitals who is authorized to carry out medical record and health information activities is a medical recorder. According to Minister of Health Regulation Number 55 of 2013 concerning the Implementation of Medical Recorder Work, medical recorder activities include carrying out patient service activities in the basic management of Medical Records and Health Information, carrying out evaluation of the contents of medical records, implementing the Clinical classification system and disease coding, implementing disease indexes, deaths and procedures, carry out evaluations of the completeness of the contents of diagnoses and procedures and carry out surveillance recording and reporting. Each activity in the medical record unit must be divided according to the competencies possessed by the medical recorder. Overall, this socialization activity ran smoothly in accordance with the activity plan that had been prepared. All participants looked enthusiastic in listening to the material presented. The method used in this activity is in the form of socialization and question and answer. Participants who took part in this activity were students of Batam Real Informatics Vocational School.